Revealing Sarcophyton extract's alleviating potential against gentamicin-induced renal and testicular toxicity in rat model - Nada S. Badr; Aml Talaat; Salwa A. El-Saidy; Aml Zaki Ahmed Ghoneim (Journal of Basic and Applied Zoology)
Abstract Background Gentamicin (GEN) is a potent antibiotic known for inducing oxidative stress and causing adverse effects in the kidneys and testes. Sarcophyton species possess significant antioxidant and anti-inflammatory properties, making them potential candidates for addressing oxidative stress and inflammation-related gentamicin toxicity. The study aims to explore the antioxidant and anti-inflammatory properties of Sarcophyton acutum methanol extract (SAME) to counteract gentamicin effects. Methods Sarcophyton acutum were collected and macerated with methanol, followed by phytochemical analysis of extract. Twenty-four adult male albino rats were separated into four equal groups: Control, SAME-treated (200 mg/kg/day), GEN-treated (100 mg/kg/day), and GEN + SAME-treated rats. Various parameters, including body weight, relative kidney and testes weight, differential white blood cell count, blood urea, creatinine, luteinizing hormone, testosterone, total antioxidant capacity, myeloperoxidase activity, and histopathological changes in kidney and testes tissue, were analyzed. Results Phytochemical analysis revealed SAME's composition, including alkaloids, saponins, phenolics, flavonoids, and tannins, with an average total antioxidant capacity of 10.503 ± 0.632 mg AAE/g extract. GEN treatment resulted in altered body and organ weights, changes in white blood cell percentages, elevated urea and creatinine levels, reduced luteinizing hormone and testosterone, decreased renal and testicular tissue total antioxidant capacity, and increased myeloperoxidase levels in both tissues. However, the administration of SAME with GEN attenuated these effects, restoring parameters closer to control levels. Histological evaluation showed that GEN treatment induced significant renal tissue damage characterized by enlarged renal corpuscles, glomerular tuft hypertrophy, tubular dilation, and necrosis, interstitial leukocyte infiltration, and tubular hyaline cast formation. Co-administration of SAME with GEN mitigated these effects, reducing renal corpuscle swelling, tubular vacuolization, and hypertrophy and preventing hyaline deposition and leukocyte infiltration. In testicular tissue, GEN injection caused seminiferous tubule atrophy, decreased spermatogenic layer thickness, and interstitial expansion and degeneration. However, SAME administration with GEN preserved normal tubular size and spermatogenic layer thickness, reduced vacuolization, and epithelial necrosis, and maintained spermatogenesis. Conclusion Sarcophyton acutum methanol extract demonstrates promising protective effects against gentamicin-induced renal and testicular toxicity in rats, signifying its potential as a therapeutic agent to mitigate antibiotic-induced oxidative damage in vital organs.